2018
DOI: 10.2147/ott.s143465
|View full text |Cite
|
Sign up to set email alerts
|

miR-134 increases the antitumor effects of cytarabine by targeting Mnks in acute myeloid leukemia cells

Abstract: The relapse and resistance to cytarabine (Ara-C) therapy is still a dominating obstacle to the successful clinical treatment of acute myeloid leukemia (AML). Recent studies have shown that dysregulation of miRNAs might modulate the resistance of cancer cells to anticancer drugs; yet, the mechanism is not fully understood. In this study, we showed a significant downregulation of miR-134 in human multidrug-resistant leukemia cells and relapsed/refractory AML patient samples. Overexpression of miR-134 sensitized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Decreases cell migration and invasion. Drug resistance [ 130 ] miR-221/ -222 MCF-7 (Tamoxifen resistant) MCF-7 (Tamoxifen-sensitive) P27 and ERα Enhances tamoxifen resistance in recipient cells. Drug resistance [ 68 ] miR-223 IL-4-activated macrophages MDA-MB-231 Mef2c- β-catenin Promotes the invasion of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Decreases cell migration and invasion. Drug resistance [ 130 ] miR-221/ -222 MCF-7 (Tamoxifen resistant) MCF-7 (Tamoxifen-sensitive) P27 and ERα Enhances tamoxifen resistance in recipient cells. Drug resistance [ 68 ] miR-223 IL-4-activated macrophages MDA-MB-231 Mef2c- β-catenin Promotes the invasion of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our hypothesis, we found that UNC1999treated cells upregulated four miRNAs (miR-494-3p, miR-130a-3p, miR-134-5p and miR-192-5p) that could functionally downregulate methionine cycling-associated genes such as MAT2A, MAT2B, CBS and CTH. Notably, these miRNAs have been reported in the context of several other cancer types [39][40][41][42][43][44][45][46][47][48] .…”
Section: Discussionmentioning
confidence: 96%
“…Especially, high dose Ara-C is a part of an induction regimen as a first-line therapy for AML [ 36 ]. However, the resistance of AML cells to Ara-C chemotherapy is one of the most important reasons for relapse or chemo-refractoriness in AML patients [ 37 ]. For that reason, combination therapy has become the standard therapy for the treatment of several different cancers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%